2015
DOI: 10.1097/mao.0000000000000757
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in Children With Autism Spectrum Disorder

Abstract: Objective To assess the outcome of cochlear implantation in children with Autism Spectrum Disorder Study Design Retrospective case review and survey Setting Tertiary referral center Patients Children who meet criteria for cochlear implantation and diagnosis of Autism Spectrum Disorder Main Outcome Measures Receptive and expressive language scores and parental survey data. Results 15 patients with history of ASD and cochlear implantation were analyzed and compared to 15 patients who received cochlear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
0
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(88 citation statements)
references
References 35 publications
2
69
0
17
Order By: Relevance
“…Another important issue is the outcomes of patients with ASDs after cochlear implantation. Limited number of studies about cochlear implantation in patients with an ASD reported satisfactory hearing outcomes, but implanted patients with ASDs still do not usually develop the expected language skills compared to those with normal neurodevelopment ( 39 , 54 ). Scientific data from ERP studies reveal that despite normal basic sensory perception, patients with ASD may have abnormal cognitive processing of auditory information, and this can explain the insufficient outcomes of language skills in this unique group of patients ( 55 , 56 , 57 , 58 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important issue is the outcomes of patients with ASDs after cochlear implantation. Limited number of studies about cochlear implantation in patients with an ASD reported satisfactory hearing outcomes, but implanted patients with ASDs still do not usually develop the expected language skills compared to those with normal neurodevelopment ( 39 , 54 ). Scientific data from ERP studies reveal that despite normal basic sensory perception, patients with ASD may have abnormal cognitive processing of auditory information, and this can explain the insufficient outcomes of language skills in this unique group of patients ( 55 , 56 , 57 , 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…After the implantation, the speech outcome can be affected because of the dual diagnoses in these patients. In a study regarding cochlear implantation in autistic individuals, Eshraghi et al ( 39 ) proposed new assessment systems for speech perception and expression scales as existing evaluation parameters would not be appropriate to assess this unique group of patients. These new scales allow to assess easily, by caregivers, the function of speech and the perception of expression.…”
Section: Central Auditory Processing Disorders and Autism Spectrum DImentioning
confidence: 99%
“…(2011) demonstrated cognitive status was the most important prognostic indicator regarding outcomes. Some researchers reported positive outcomes in either speech perception skills and/or language development skills for populations with a specific disability, such as cerebral palsy ( Steven et al., 2011 , Lamônica et al., 2014, June ), Usher syndrome type 1 ( Henricson et al., 2012 ), congenital cytomegalovirus infection accompanied by psycho-neurological disorders ( Yamazaki et al., 2012 ), CHARGE syndrome ( Birman et al., 2015 ), and autism spectrum disorders ( Meinzen-Derr et al., 2014 , Eshraghi et al., 2015 ). Further research is required to help guide expected outcomes of implantation of this diverse population.…”
Section: From Excluding Children With Disabilities To Special Studiesmentioning
confidence: 99%
“…First, some children with secondary issues can complete speech perception tasks. For example, Eshraghi et al (2015) found that two-thirds of children with autism spectrum disorder using CIs can at least identify or recognize simple phrases, an early-developing auditory skill, per parent report. Second, eliminating children with secondary disabilities from research studies hinders our ability as clinicians to identify suitable expectations and appropriate recommendations for supplemental technology (such as home FM use) and outcomes assessment in these children.…”
mentioning
confidence: 99%